Terminal osteoblast differentiation, mediated by runx2 and p27KIP1, is disrupted in osteosarcoma - David M. Thomas; Sandra Johnson; Natalie A. Sims; Melanie Trivett; John Slavin; Brian P. Rubin; Paul Waring; Grant A. McArthur; Carl R. Walkley; Andrew Holloway; Dileepa Diyagama; Jonathon E. Grim; et al. (2004)
The molecular basis for the inverse relationship between differentiation and tumorigenesis is unknown. The function of runx2, a master regulator of osteoblast differentiation belonging to the runt family of tumor suppressor genes, is consistently disrupted in osteosarcoma cell lines. Ectopic expression of runx2 induces p27KIP1, thereby inhibiting the activity of S-phase cyclin complexes and leading to the dephosphorylation of the retinoblastoma tumor suppressor protein (pRb) and a G1 cell cycle arrest. Runx2 physically interacts with the hypophosphorylated form of pRb, a known coactivator of runx2, thereby completing a feed-forward loop in which progressive cell cycle exit promotes increased expression of the osteoblast phenotype. Loss of p27KIP1 perturbs transient and terminal cell cycle exit in osteoblasts. Consistent with the incompatibility of malignant transformation and permanent cell cycle exit, loss of p27KIP1 expression correlates with dedifferentiation in high-grade human osteosarcomas. Physiologic coupling of osteoblast differentiation to cell cycle withdrawal is mediated through runx2 and p27KIP1, and these processes are disrupted in osteosarcoma.